SHORT HISTORICAL NOTES XVII - Anton Gajdoš (University of Ljubljana Press (Založba Univerze v Ljubljani), 2020)
NIKOLAI YEFIMOVIČ ANDRIANOV (14 October 1952, Vladimir, Russia - 21 March 2011, Vladimir, Russia)